Association between pesticide exposure and childhood leukaemia: a systematic literature review of epidemiological studies - Sidek Ahmad, Zulkhairul Naim; Che Hasan, Muhammad Kamil (IIUM Press, 2020)
Introduction: Cancer is the leading cause of death for children and adolescents globally with 300,000 children aged 0-19 are diagnosed with cancer every year, mainly leukaemia, lymphomas and brain cancers. Like other causes of cancer, the difficulty arises because of multi-factorial aetiologies involving the interaction between genetic factors as well as environmental exposures. Aims: This study aimed to analyse published studies on the relationship between childhood leukaemia and exposures to pesticides. Methods: The search on the literature database Ovid-MEDLINE search strategy was conducted for the period from 1995 to 2014. The quality of non-randomised studies was assessed by using Newcastle Ottawa Scale (NOS). Results: Six studies investigated the relationship related to parental residential exposure and one study, showed an association between childhood leukaemia and maternal exposure. Two studies investigated the relationship to maternal residential exposure. Two studies reported an association between childhood leukaemia and parental occupational exposure. One study showed a positive association out of two studies that evaluated the association related to parental occupational and residential exposure. This review provides evidence of weak to modest association between childhood leukaemia and pesticides exposure in most of the studies. Conclusion: Most studies showed an association; however, the causation remains unexplained because of limitations such as potential bias, faulty study design and sample frame, lack of statistical power and also ascertainment of exposure.